The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3390/atmos8010001
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Regression Modeling of PM2.5 Concentrations at Optimized Spatial Scales

Abstract: Though land use regression (LUR) models have been widely utilized to simulate air pollution distribution, unclear spatial scale effects of contributing characteristic variables usually make results study-specific. In this study, LUR models for PM 2.5 in Houston Metropolitan Area, US were developed under scales of 100 m, 300 m, 500 m, 800 m, and 1000-5000 m with intervals of 500 m by employing the idea of statistically optimized analysis. Results show that the annual average PM 2.5 concentration in Houston was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…According to the previous LUR research findings on the selection of geographical feature characteristics [14,[29][30][31], data collected for LUR modelling in this study contains annual average PM2.5 concentrations, elevation, AOD, climate characteristics (temperature, wind speed, relative humidity, atmospheric pressure, and precipitation), road traffic, land use and cover, industrial plants, and surface dust. The distribution of PM2.5 monitoring sites and the partial basic geographical feature data, within the BTH region during the study period of 1 January 2015 to 31 December 2015, are shown in Figure 1.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the previous LUR research findings on the selection of geographical feature characteristics [14,[29][30][31], data collected for LUR modelling in this study contains annual average PM2.5 concentrations, elevation, AOD, climate characteristics (temperature, wind speed, relative humidity, atmospheric pressure, and precipitation), road traffic, land use and cover, industrial plants, and surface dust. The distribution of PM2.5 monitoring sites and the partial basic geographical feature data, within the BTH region during the study period of 1 January 2015 to 31 December 2015, are shown in Figure 1.…”
Section: Study Area and Data Collectionmentioning
confidence: 99%
“…The characteristic values were extracted at a 100-10,000 m (100, 200, 400, 500, 600, 800, 1000, 2000, 3000, 4000, 5000, 6000, 8000, and 10,000 m) buffering radius based on previous findings and experiments [10,14,29]. Moreover, the distance to a nearest road or industrial plant, elevation, the annual averages of AOD, as well as the annual averages of climate characteristics, were also included as the potential predictor variables in this study.…”
Section: Predictor Variable Extraction and Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…The types of land use included woodland, residential, industrial, commercial, urban greenery, transportation, agricultural, bare land, waters, and roads. Buffers were created for 100, 300, 500, 800, 1000, 2000, 3000, 4000, and 5000 m, according to previous research findings [23][24][25]. Using version 4.2 of FRAGSTATS [10,26], We calculated landscape pattern index [27] of different distance buffers for analysis ( Table 1).…”
Section: Independent Variablesmentioning
confidence: 99%
“…The variables that were highly relevant (R > 0.6) to the selected factor were eliminated, and the variables with correlations different from historical experiences were removed [18]. By comparing the prediction accuracy of forward, backward, and stepwise selection, we found that the prediction accuracy of stepwise selection was higher [25,[28][29][30]. All variables that satisfied the requirements were subjected to stepwise multivariate linear regression along with the PM 2.5 concentration.…”
Section: Model Development and Evaluationmentioning
confidence: 99%